Business Model Canvas dan Unified Modelling Language untuk Desain E-Commerce Toko Bintangsprei11 - Saputra, Achmat Jodi; Ariesta, Atik (Informatik : Jurnal Ilmu Komputer, 2022)
Bintangsprei11 is an online store that was formed in 2019 by selling products in the form of bedding equipment which are 99% made of CVC cotton, namely bed linen and bedcovers. These sheets and bedcovers are homemade. The problems faced by Bintangsprei11 are that the Bintangsprei11 Store sells on the Shopee marketplace where each transaction will be subject to a tax fee of 2.5% from each product sale, this Bintangsprei11 Store in a month can pay taxes of approximately 600 thousand per month. The rating on the Bintangsprei11 store is 4.9 and reviews from customers are 400 ratings. In the Marketplace used, Shopee Toko Bintangsprei11 has many competitors selling similar products. Based on the existing problems, an e-commerce website is needed to facilitate the marketing of products sold and get closer to customers. In designing this e-commerce website using Business Model Canvas (BMC) to analyze business development models and Unified Modeling Language (UML) for system analysis and design. In making this Bintangsprei11 website, we used an open-source WordPress web application based on the Content Management System (CMS) with the WooCommerce plugin. This designed e-commerce website can facilitate product promotion, increase revenue, customers can search for products that are sold, minimize seller expenses and make it easier for admin/owners on Bintangsprei11